Development of Two-Dimensional Figure Jenga Media to Improve Students’ Learning Outcome in Elementary School - Kowiyah; Anindita Margiaty (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of this research develops Two-Dimensional Figure Jenga Media which is valid, practical, and effective to improve the students’ learning outcome of class IV in Mathematic lesson. The method used is Research and Development by applying a 4D model which has four stages including Define, Design, Develop and Disseminate. The test subjects for this research were 25 grade IV students at SDN Batu Ampar 02. The data collection technique used included media validation, material validation, language validation, teacher response questionnaires, student response questionnaires and student learning outcome tests. Analysis of the effectiveness of the Two-Dimensional Figure Jenga media used a paired sample T Test which was previously carried out for normality and homogeneity tests as a prerequisite test. The research results for the validity assessment assessed by the Media Validator obtained a score of 89% in the very good category, the Material Validator obtained a score of 89% in the very good category and the Language Validator obtained a score of 78% in the good category. Practicality assessment after being tested based on the value given by the class teacher obtained a score of 98%, and the average gain in small group trials was 97% and large group trials was 87%. Effectiveness assessment based on learning outcome test obtained an average pre-test score of 56.8 and post-test 75.6, as well as the results obtained from normality test calculations, the pre-test sig value was 0.209 and post-test 0.183 > 0.05 indicating that the data is normally distributed. The pre-test and post-test homogeneity test calculations are sig 0.347 and 0.172 > 0.05, which means the data is homogeneous. The paired sample t test calculation is sig (2-tailed) 0.000 < 0.05, which means that the Two-Dimensional Figure Jenga media has an influence on learning outcome. So, Two-Dimensional Figure Jenga media can be said to be suitable for use to improve learning outcome during the learning process.